2017
DOI: 10.1007/s11912-017-0643-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Malignant Pheochromocytomas and Paragangliomas: 5 Years of Progress

Abstract: The manuscript will describe the clinical predictors of survivorship and their influence on the first TNM staging classification for pheochromocytomas and sympathetic paragangliomas, the treatment of hormonal complications, and the rationale that supports the resection of the primary tumor and metastases in patients with otherwise incurable disease. Therapeutic options for patients with bone metastasis to the spine will be presented. The manuscript will also review chemotherapy and propose a maintenance regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 70 publications
0
59
0
1
Order By: Relevance
“…CVD chemotherapy can be indicated to treat patients presenting an evolutive disease, and the patients who well respond to CVD can gain from a maintaining treatment with the dacarbazine. Clinical trials are ongoing for the use of radio-pharmaceutical agents, inhibitors of tyrosine kinase and immunotherapies [20].…”
Section: Discussionmentioning
confidence: 99%
“…CVD chemotherapy can be indicated to treat patients presenting an evolutive disease, and the patients who well respond to CVD can gain from a maintaining treatment with the dacarbazine. Clinical trials are ongoing for the use of radio-pharmaceutical agents, inhibitors of tyrosine kinase and immunotherapies [20].…”
Section: Discussionmentioning
confidence: 99%
“…Pheochromocytomas embolization alone has proved to be insufficient for long-term symptom and hormone control and surgical resection remains the gold standard of treatment, also because approximately 15-17% of pheochromocytomas are discovered to be malignant at the pathological examination (145).…”
Section: Adrenal Hormone Suppressionmentioning
confidence: 99%
“…Besides other sporadically-used chemotherapy protocols including cisplatin, 5-fluorouracil, methotrexate, ifosfamide and streptozotocin which show low evidence to support their clinical use [54,55], the best studied chemotherapy protocol for advanced PCC/PGL combines cyclophosphamide, vincristine, and dacarbazine (CVD) according to the Averbuch scheme (cyclophosphamide 750 mg/ m 2 , vincristine 1.4 mg/m 2 , and dacarbazine 600 mg/m 2 on day 1 and dacarbazine 600 mg/m 2 on day 2) [56]. However, all studies are retrospective and prognostic factors indicating metastatic behaviour such as size and location of the primary tumour, size, location and the timing of metastases, progression prior to chemotherapy, and SDHB mutation status, are frequently missing [55]. A meta-analysis of the largest studies on CVD showed a partial response concern-ing tumour size in 37 % of patients [57].…”
Section: Chemotherapy: Classic Chemotherapy Updatedmentioning
confidence: 99%
“…However, the side effects of vincristine may include peripheral sensory and autonomic neuropathy [63] while rare cases of leukaemia and myelodysplastic syndrome have been observed [58]. Whether adjuvant treatment with 4-6 cycles of CVD after surgery in patients with positive predictors of metastatic potential could improve PFS and OS has not yet been studied [55].…”
Section: Chemotherapy: Classic Chemotherapy Updatedmentioning
confidence: 99%
See 1 more Smart Citation